If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (P + -2)(3p + 7) = 0 Reorder the terms: (-2 + P)(3p + 7) = 0 Reorder the terms: (-2 + P)(7 + 3p) = 0 Multiply (-2 + P) * (7 + 3p) (-2(7 + 3p) + P(7 + 3p)) = 0 ((7 * -2 + 3p * -2) + P(7 + 3p)) = 0 ((-14 + -6p) + P(7 + 3p)) = 0 (-14 + -6p + (7 * P + 3p * P)) = 0 (-14 + -6p + (7P + 3pP)) = 0 Reorder the terms: (-14 + 7P + -6p + 3pP) = 0 (-14 + 7P + -6p + 3pP) = 0 Solving -14 + 7P + -6p + 3pP = 0 Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 7P + -6p + 14 + 3pP = 0 + 14 Reorder the terms: -14 + 14 + 7P + -6p + 3pP = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 7P + -6p + 3pP = 0 + 14 7P + -6p + 3pP = 0 + 14 Combine like terms: 0 + 14 = 14 7P + -6p + 3pP = 14 Add '6p' to each side of the equation. 7P + -6p + 6p + 3pP = 14 + 6p Combine like terms: -6p + 6p = 0 7P + 0 + 3pP = 14 + 6p 7P + 3pP = 14 + 6p Reorder the terms: -14 + 7P + -6p + 3pP = 14 + 6p + -14 + -6p Reorder the terms: -14 + 7P + -6p + 3pP = 14 + -14 + 6p + -6p Combine like terms: 14 + -14 = 0 -14 + 7P + -6p + 3pP = 0 + 6p + -6p -14 + 7P + -6p + 3pP = 6p + -6p Combine like terms: 6p + -6p = 0 -14 + 7P + -6p + 3pP = 0 The solution to this equation could not be determined.
| x=7+2t | | 2.75d-4.5=2.25d+3.5 | | x-7=2t | | 3*-3*9= | | 7x-7w+2y+5w+5x+9y= | | 10r^2-53r+36=0 | | 7.2x-14.1=7.5 | | 7p^2-2p=5 | | 7(x-3)=4x-14 | | 6*(-4)= | | 54x+98y=21x | | 3xz+6=2x-1 | | (c+9)(c+5)=-3 | | 4x+5x-7=2 | | 6=-5k+6k | | X^8-13=0 | | 5x+18+x=180 | | .5x-.7=6.3 | | -73=-8+5p | | 10y+4x=20 | | 5n^2-36n+57=0 | | 159=5(7+4n)+4 | | 9p-9=2(2p+8) | | 20=7-x | | -256=8(7b-4) | | 28=3w+4w | | 6x-27=17 | | 6x+4=-92 | | x^4-60+2x^2=-2x^4-x^2 | | 23=3w+4w | | 5(2d+3)=45 | | 5x+14=79 |